Economic Analysis of the Pearl River Delta’s "Labor Shortage" - Xiao-ran, LI; Yan-ming, HE; Cheng-cheng, WU (Asian Business Review, 2014)
The shortage of workers in the Pearl River Delta is becoming increasingly severe. The enterprise can hardly employ enough workers. Based on the supply-demand model, this paper analyzes the phenomenon from the view of economic, and bases on the Lewis Model analyze the deep cause of this situation. This paper argues that the best way to solve this problem is to speed up the industry transition and upgrading, improve the post technical content, in order to radically reduce labor demand.